The Effectiveness of Blog as Media in Improving The Students‟ Writing Skill of Descriptive Text (An Experimental Study of the Eight Graders of MTsN Brangsong Kendal in the Academic Year of 2013/2014 - Hidayaturrahman, Thoriq (LPPM Universitas Mercu Buana Yogyakarta, 2015)
This study aimed at comparing students‟ ability in writing descriptive text withblogtechnique and without blog. This study is used to answer the questions: Is thereany significant difference in the achievement between the students who wrotedescriptive text with blogtechnique and the students who wrote descriptive text withoutblog? And how well the students write descriptive text after being taught by using blog.Quantitative method was used in analyzing the gathered data. The basic outline showedthat in the writing skill, the second year students in the first semester of Junior HighSchool are supposed to write a descriptive text, so the data weredescriptive textswritten by two classes of the second year students of MTs Brangsong Kendal as thesample. One of them was the experimental group and the other one was the controlgroup. The result of the study shows that Blog technique applied in writingdescriptiontexts of VIIIgrade of MTs Brangsong, Kendal, actually gave contribution in improvingthe students‟ skill in writing descriptive texts. This technique could be an effectivemethod. It is proper since there was a significant difference between the control groupand the experimental group when the study was conducted. Based on the statisticalanalysis, it could be seen that the students‟ in the experimental group was improvinghigher than the control group. The mean of the experimental group was higher (from71.81to 80.11) than the control group (from 71.72 to 74.61). The t-value for two meansof post-test was 4.170; meanwhile the critical value at α = 5% was 1.67. Since the tvaluewas in the Ho rejection area, it was concluded that there is a significantdifference in the achievement between the students in control group who were not giventhe treatment and the experimental group who were given the treatment (Blogtechnique). By using this technique in the experimental class, the class situation wasvery enjoyable, the students freely communicated to each other to share their ideas.The writer had observed that the writing descriptive texts scores of the experimentalclass were higher than those of the students who wrote descriptive text without Blog.Keywords: Blog, Descriptive Text, WritingSkill